Owner observations regarding cat scratching behavior: an internet-based survey. Issue 10 (October 2016) - Wilson, Colleen; Bain, Melissa; DePorter, Theresa; Beck, Alexandra; Grassi, Vanessa; Landsberg, Gary
Objectives: This study was performed to examine aspects of the cat, environment and scratching post that might influence scratching behavior, in an effort to determine how inappropriate scratching behavior might be refocused on acceptable targets. Methods: An internet survey, posted on several public websites, gathered details about scratching behavior, as described by owners in their home environments, from 4331 respondents over a 4 month period. Responses from 39 different countries were analyzed, mostly from the USA, Canada and the UK. Results: Owners offered traditionally recommended scratching substrates including rope, cardboard, carpet and wood. Rope was most frequently used when offered, although carpet was offered most commonly. Most owners provided at least one scratching post; cats scratched the preferred substrate more often when the post was a simple upright type or a cat tree with two or more levels and at least 3 ft high. Narrower posts (base width ⩽3 ft) were used more often than wider posts (base width ⩾5 ft). Intact or neutered cats (males and females) were as likely to scratch inappropriately, and inappropriate scratching decreased with age. Geriatric cats between the ages of 10 and 14 years preferred carpet substrate most frequently; all other ages preferred rope first. Inappropriate scratching decreased as the different types/styles of posts increased in the home. Inappropriate scratching did not increase if the number of cats or dogs increased in the household. Declawed cats were preventatively declawed most often to prevent household item destruction. Conclusions and relevance: Although cats can have individual preferences, our data provide a starting point for veterinarians recommending scratching posts to clients.